The Governance of Style : Public buildings in Central Europe, 1780-1920 - Hartmuth, Maximilian; Kurdiovsky, Richard; Vasold, Georg; Rüdiger, Julia (2023)
Abstract The architecture of some public buildings exhibits a commitment to economic restraint and a subordination to an international aesthetic of dutifulness. Other public buildings exhibit a heightened sensitivity to place – to topography, architectural setting, and select cultural inheritances. The decision-making processes that led up to the implementation of such projects are often insufficiently appreciated. The 20 contributions to this volume, focused on Central Europe, address the problem of defining and locating public buildings as architectural expressions in a protracted period of transition between feudal and modern constitutional social orders.